Tourism Information System In Pringsewu Regency Using Mobile Web-Based Geographic Information System (GIS) - Nina Risti Ultimate; Muhtarom Muhtarom (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Study this aim for build application information p aritourism with geographic information s is tem and invite you to visit a wan in get information tour in K district Pringsewu with take advantage of smart smartphones. By kar e na that writer do study about application information tourism mobile web -based in the District Pringsewu. Method used in study this is type study applied. Location study done on the spot tourism in the district Pringsewu. Data source obtained from visit live place tour t a to use get information. Technique data collection carried out with method interview, observation, documentation. From the results of the research that has been done, it can be concluded that with exists s i stem information geographic web-based mobile visitors could knowing information the place tourism in Pringsewu and knowing information about the place tourist at a time knowing direction towards the place tourism you want visited.